Application of Numbered Head Together (NHT) Cooperative Learning Models in Improving Learning Outcomes on Social Problems In Grade IV of Elementary School - Musdiani, Musdiani; Mardhatillah, Mardhatillah; Kasmini, Lili; Marlini, Cut; Fuad, Zaki Al; Helminsyah, Helminsyah; Subhananto, Aprian (Jurnal Ilmiah Teunuleh, 2023)
Model cooperative learning Numbered Head Together (NHT) in teaching and learning activities in social studies with the subject matter of the social problems in the fourth grade Elementary School Superior Lampeuneurut. The formulation of this research through cooperative learning increases learning motivation, self-confidence. The purpose of this study is to determine learning motivation, self-confidence and improve student learning outcomes. Classroom Action Research (PTK) in grade IV SD Negeri Unggul Lampeuneurut students were carried out in two cycles. Each cycle consists of four stages, namely planning, implementing, acting, observing and reflecting. The results of this study obtained Activities teachers during the first cycle obtained an average score of 3, 61 (72.30%), including both categories and activities students gain an average score of 3.38 (67.5%) were included in both categories. Activities during the second cycle teachers earn an average score of 4, 54 (90.90%) and included in the excellent category. Activity of students during cooperative learning NHT in the second cycle obtain an average value of 4, 5 (90%) including category very well. Based on the results of the research and discussion, it can be concluded that learning social problems by applying the cooperative model type NHT increases the completeness of learning outcomes in grade IV students. SD Negeri Unggul Lampeuneurut. The increase in the average acquisition score of the first cycle of 65, 83 (54.16%), the second cycle of 75.83 (66.66%) increased by 12.5%.